Penyuluhan Kesehatan Narkotika: Jenis, Manfaat dan Penyalahgunaannya di SMA Negeri 04 Makassar - Vina Purnamasari M; Ririn; Herman, Hendra (Cahaya Pengabdian, 2024)
Drug abuse has broad and complex dimensions, both from a medical, psychiatric, mental health, and psychosocial perspective. Counseling efforts are a method that is carried out to prevent the circulation and abuse of NAPZA. The approach must be carried out directly to students or adolescents regardless of parental, school, and, community supervision. This counseling activity aims to increase student awareness of the dangers of drug abuse. Community service is carried out in 6 stages of implementation, namely: Socialization of community service activities to be carried out, Introduction to the types of Narcotics to all participants in this case partners, Design of time and activity models with partners, Implementation of counseling on the dangers of narcotics, psychotropics, and addictive substances to students and teachers, Workshop on making media for socializing the dangers of drugs to students, Evaluation of activities. Community service activities were attended by 32 participants as representatives of youth groups from grade 3 students of SMAN 04 Makassar. From the results of the training and counseling during the process, it can be seen that the participants responded enthusiastically with their activeness in watching and following the counseling and training, and not infrequently participants asked questions and had small discussions during the entire activity. Both in the Q&A session and on other occasions.